STUDY ON CHANGES OF SPERM HEAD MORPHOMETRY AND DNA INTEGRITY OF FREEZE-DRIED BOVINE SPERMATOZOA - Said, S.; Afiati, F.; Maulana, T. (Diponegoro University, 2015)
Changes of sperm heads morphometric and DNA integrity of freeze-dried bovine spermatozoa were investigated. Freeze-dried spermatozoa had stored in the refrigerator at 4°C for 2 years. Computer-assisted sperm analysis (CASA) was used in this study to identify sperm head morphometry, while for DNA integrity analysis using acridine orange staining. Samples were smeared on glass slides, fixed for 2 h in acetic alcohol and stained with acridine orange solution. After staining, each slide was examined at x400 magnification in a fluorescence microscope with axio vision (Zeiss Company, Germany). Proportion of fluorescence red and green emissions of the sperm head were examined and scored. These results indicated that sperm head had enlarged significantly (P<0.05) after freeze-drying process. However, freeze-dried sperm heads morphometry significantly (P<0.05) decrease after incubation for 3 and 6 hours. Changes of DNA integrity of freeze-dried spermatozoa significantly (P<0.05) decrease after incubation for 6 hours. In the present study concluded that (1) freeze-drying spermatozoa caused sperm head morphometric enlarged, whereas incubation time caused sperm heads decreased, (2) DNA integrity of freeze-dried sperm head is still intact during incubation 3 hours, and decreased DNA integrity occur in incubation for 6 hours.